الملوحة مشكلة عالمية تهدد الأمن الغذائي في المناطق الجافة - ملازم, سلمه; حروشي, آسيا; دحمري, مروة; عطاالله, خولة (جامعة الوادي - University of Eloued, 2022)
Salinity is considered one of the most important problems that afflict lands in dry areas, as it constitutes a real threat to food security there. To clarify this problem more, we conducted a theoretical study of it and presented some solutions in it, as we reached the following:  Dry areas are the most vulnerable to salinity, agricultural crops in these areas, in addition to suffering from drought stress, suffer from salt stress, which affects their productivity and thus food security is affected.  Salt stress changes the phenotypic and functional indicators of the plant.  Modern methods of land reclamation are water preparation, saline preparation, hormonal preparation and others, which are effective methods for solving the problem of salinity.  Also among the solutions to reduce the danger of salinity to food security is saline agriculture, which depends on the use of saline water and soils to grow salt-tolerant crops.
التنوع الحيوي وفيزيولوجيا النبات
Keywords: food security; dry areas; salinity; salinity stress; land reclamation; saline agriculture.; الأمن الغذائي، المناطق الجافة، الملوحة، الإجهاد الملحي، استصالح الأراضي، الزراعة الملحية